Minimally invasive and transcatheter techniques in high-risk cardiac surgery patients. (April 2012) - Sündermann, Simon H; Scherman, Jacques; Falk, Volkmar
Minimally invasive procedures have become pivotal in cardiac surgery, especially for the ever-increasing group of high-risk patients. These procedures are defined by the surgical access and/or the avoidance of cardiopulmonary bypass. Both of these aspects have been shown to be beneficial for patients with an increased perioperative risk. For high-risk patients with coronary artery disease, off-pump coronary artery bypass surgery via various surgical access routes can be performed. For patients with heart valve disease, minimally invasive approaches are routinely used in the clinic. During the last decade, interventional methods to treat aortic and mitral valve disease including transcatheter aortic valve replacement and the MitraClip were developed. These modalities have provided clinicians with the ability to treat patients with very high operative risk that are considered not fit for conventional surgery.